Comparison of Lipid Lowering Effect of Aqueous Extract of Cinnamon (Cinnamomum Cassiae) with that of Rosuvastatin on Experimentally Induced Hypercholesterolaemic Rats (TAJ: Journal of Teachers Association, 2019)
Background: Hypercholesterolemia is a condition characterized by very high level of cholesterol in the blood. Too much cholesterol increases risk of developing heart disease called coronary artery disease. This condition occurs when excess cholesterol in the bloodstream is deposited in the walls of blood vessels, particularly in the coronary arteries that supply blood to the heart. A phenolic compound of the cinnamon extract lowers serum lipid level by inhibiting HMG COA reductase & by activation of nuclear receptor peroxisome proliferator activated receptor alpha (PPAR-α). We are trying to evaluate the lipid lowering effect of cinnamon (Cinnamomum cassiae) in comparison with rosuvastatin in hypercholesterolaemic rats.Aim: To find out the lipid lowering effect of aqueous extract of cinnamon (Cinnamomum cassiae) and compare it with a established lipid lowering drug (rosuvastatin) on hypercholesterolaemic rats.Method: This was a experimental study conducted in the department of Pharmacology, Dhaka medical college & Hospital from July 2015 to June 2016. Sample size was 30.The study was designed as 2 parts: Experiment-1 & Experiment -2.Result: Cinnamon produces no statistically significant effect on serum lipid level of healthy rats (P- value >0.05; which is not significant). Cinnamon significantly reduced serum lipid level of high cholesterol diet induced hypercholesterolaemic rats. But, there is statistically significant difference between cinnamon and rosuvastatin lipid lowering effect in high cholesterol diet induced hypercholesterolaemic rats (p value